Scattering of Charge Carriers in Thin Films PbTe:Bi - R. Dzumedzey (Фізика і хімія твердого тіла, 2019)
The calculations of the scattering mechanisms of charge carriers in thin films of PbTe:Bi with 1 at. % of bismuth is carried out. The dominant mechanisms of scattering in the investigated samples are determined. The thickness dependence of the ratio msurf/mbulk is considered.